Clinical utility of routine laboratory testing to identify possible secondary causes in older men with osteoporosis: the Osteoporotic Fractures in Men (MrOS) Study. Issue 1 (January 2016) - Fink, H.; Litwack-Harrison, S.; Taylor, B.; Bauer, D.; Orwoll, E.; Lee, C.; Barrett-Connor, E.; Schousboe, J.; Kado, D.; Garimella, P.; Ensrud, K.
Abstract Summary We investigated the value of routine laboratory testing for identifying underlying causes in older men diagnosed with osteoporosis. Most osteoporotic and nonosteoporotic men had ≥1 laboratory abnormality. Few individual laboratory abnormalities were more common in osteoporotic men. The benefit of routine laboratory testing in older osteoporotic men may be low. Introduction To evaluate the utility of recommended laboratory testing to identify secondary causes in older men with osteoporosis, we examined prevalence of laboratory abnormalities in older men with and without osteoporosis. Methods One thousand five hundred seventy-two men aged ≥65 years in the Osteoporotic Fractures in Men study completed bone mineral density (BMD) testing and a battery of laboratory measures, including serum calcium, phosphorus, alkaline phosphatase, parathyroid hormone (PTH), thyroid-stimulating hormone (TSH), 25-OH vitamin D, total testosterone, spot urine calcium/creatinine ratio, spot urine albumin/creatinine ratio, creatinine-derived estimated glomerular filtration rate, 24-h urine calcium, and 24-h urine free cortisol. Using cross-sectional analyses, we calculated prevalence ratios (PRs) and 95 % confidence intervals (CI) for the association of any and specific laboratory abnormalities with osteoporosis and the number of men with osteoporosis needed to test to identify one additional laboratory abnormality compared to testing men without osteoporosis. Results Approximately 60 % of men had ≥1 laboratory abnormality in both men with and without osteoporosis. Among individual tests, only vitamin D insufficiency (PR, 1.13; 95 % CI, 1.05–1.22) and high alkaline phosphatase (PR, 3.05; 95 % CI, 1.52–6.11) were more likely in men with osteoporosis. Hypercortisolism and hyperthyroidism were uncommon and not significantly more frequent in men with osteoporosis. No osteoporotic men had hypercalciuria. Conclusions Though most of these older men had ≥1 laboratory abnormality, few routinely recommended individual tests were more common in men with osteoporosis than in those without osteoporosis. Possibly excepting vitamin D and alkaline phosphatase, benefit of routine laboratory testing to identify possible secondary causes in older osteoporotic men appears low. Results may not be generalizable to younger men or to older men in whom history and exam findings raise clinical suspicion for a secondary cause of osteoporosis.